2019
DOI: 10.5586/asbp.3611
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel and conserved microRNAs involved in fruit development and ripening in Fragaria vesca

Abstract: MicroRNAs (miRNAs) are class of noncoding RNAs that regulate gene expression at the post-transcriptional level, either by endonucleolytic cleavage or by translational inhibition. Strawberry is a popular worldwide fresh fruit and is believed to benefit human health. However, the function of miRNAs during this fruit development and ripening remains unknown and miRNAs for specific for these processes are expected to be discovered. In the study, we identified 218 conserved miRNAs and 87 novel miRNAs in <em>F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Compared with the annotated miRNAs of miRBase, we found that the raspberry miRNAs were relatively conserved with those of higher model and closely relative plants, such as Arabidopsis (Wang et al, 2004), Fragaria vesca (Han et al, 2019), Zea mays (Aydinoglu and Lucas, 2019), and sweet cherry (Wang et al, 2019). A large number miRNAs, such as miR159, miR157 and miR394 have similar base composition with miRNAs in closely relative plants.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Compared with the annotated miRNAs of miRBase, we found that the raspberry miRNAs were relatively conserved with those of higher model and closely relative plants, such as Arabidopsis (Wang et al, 2004), Fragaria vesca (Han et al, 2019), Zea mays (Aydinoglu and Lucas, 2019), and sweet cherry (Wang et al, 2019). A large number miRNAs, such as miR159, miR157 and miR394 have similar base composition with miRNAs in closely relative plants.…”
Section: Discussionmentioning
confidence: 86%
“…In recent years, miRNAs have been identified in some plants species through cloning and computational approaches (Saliminejad et al, 2019;Smoczynska et al, 2019), and it has also been shown that miRNAs may be predicted using modern machine learning approaches (Parveen et al, 2019;Esposito et al, 2020). Recent reports have identified hundreds of miRNAs in several species, including Fragaria vesca (Han et al, 2019), cardamom (Anjali et al, 2019), sweet cherry (Wang et al, 2019), and Brazilian pine (Galdino et al, 2019) through highthroughput sequencing. Currently, 38,589 entries representing hairpin precursor miRNAs and 48,860 mature miRNAs have been discovered from 271 organisms, and these are available in the public miRNA database miRbase (Release 22.1, October 2018) 1 (Kozomara et al, 2018).…”
Section: Introductionmentioning
confidence: 99%